2023
DOI: 10.3390/ijms241914940
|View full text |Cite
|
Sign up to set email alerts
|

p53 in the Molecular Circuitry of Bone Marrow Failure Syndromes

Jeanne Rakotopare,
Franck Toledo

Abstract: Mice with a constitutive increase in p53 activity exhibited features of dyskeratosis congenita (DC), a bone marrow failure syndrome (BMFS) caused by defective telomere maintenance. Further studies confirmed, in humans and mice, that germline mutations affecting TP53 or its regulator MDM4 may cause short telomeres and alter hematopoiesis, but also revealed features of Diamond–Blackfan anemia (DBA) or Fanconi anemia (FA), two BMFSs, respectively, caused by defects in ribosomal function or DNA repair. p53 downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…However, the fact that two different ultrarare variants were found in this gene in three cases from two families increases the likelihood they are playing a role. Interestingly, FC proteins interact with components of the p53 DDR pathway, including ATM and ATR (Figure 2) [122][123][124][125] . Some researchers have suggested that autoimmune and/or autoinflammatory processes underlie the development of behavioral regression in PANS and in a subgroup of individuals with ASD 35,[126][127][128] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fact that two different ultrarare variants were found in this gene in three cases from two families increases the likelihood they are playing a role. Interestingly, FC proteins interact with components of the p53 DDR pathway, including ATM and ATR (Figure 2) [122][123][124][125] . Some researchers have suggested that autoimmune and/or autoinflammatory processes underlie the development of behavioral regression in PANS and in a subgroup of individuals with ASD 35,[126][127][128] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FC proteins interact with components of the p53 DDR pathway, including ATM and ATR (Figure 2) [126][127][128][129] . Some researchers have suggested that autoimmune and/or autoinflammatory processes underlie the development of behavioral regression in PANS and in a subgroup of individuals with ASD 34,[130][131][132] .…”
Section: Discussionmentioning
confidence: 99%